2022
DOI: 10.1007/s40266-022-00966-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hypertension in the Elderly and Frail Patient

Abstract: Hypertension is a frequent finding in elderly patients. Hypertension in older age can be both associated with frailty and represent a risk factor for frailty. Hypertension is recognized as a main risk factor for cardiovascular diseases such as heart failure, atrial fibrillation, and stroke and the occurrence of these diseases may provoke a decline in health status and/or worsen the degree of frailty. Blood pressure targets in hypertensive older and frail patients are not completely defined. However, specific e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 109 publications
0
6
1
5
Order By: Relevance
“…In addition, evidence showed that frailty was closely associated with cardiovascular events. 16 Patients aged ≥65 years had higher NT-proBNP values, and a lower proportion of them achieved the target goal of LVEF (≥50%) in the present study. Similar to previous statistics, 17 the incidence of new or recurrent cardiovascular events was remarkably elevated among the elderly patients (≥65 years) compared with the others (<65 years).…”
Section: Discussioncontrasting
confidence: 53%
“…In addition, evidence showed that frailty was closely associated with cardiovascular events. 16 Patients aged ≥65 years had higher NT-proBNP values, and a lower proportion of them achieved the target goal of LVEF (≥50%) in the present study. Similar to previous statistics, 17 the incidence of new or recurrent cardiovascular events was remarkably elevated among the elderly patients (≥65 years) compared with the others (<65 years).…”
Section: Discussioncontrasting
confidence: 53%
“…An exceedingly low BUN/Cr ratio indicates a state of hyperhydration, leading to an augmented cardiovascular preload and elevated blood pressure. Consequently, this escalation in cardiovascular strain heightens the susceptibility to heart failure and stroke ( 27 ). A diminished BUN/Cr ratio is correlated with heightened risks of total incident stroke and ischemic stroke ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Di Indonesia sendiri, 23,7% dari 1,37 juta kematian di Indonesia pada tahun 2016 disebabkan oleh hipertensi. (Guasti et al, 2022;Kemenkes RI P2PTM, 2019;Shah & Stafford, 2017;Zhou et al, 2021) Bruno et al melaporkan adanya perubahan fisiologi pada pembuluh darah pada orang tua dan kontribusinya terhadap hipertensi. Hal ini membuat peneliti tertarik untuk mempelajari korelasi hipertensi dengan usia.…”
Section: Latar Belakangunclassified